2021
DOI: 10.1155/2021/8862456
|View full text |Cite
|
Sign up to set email alerts
|

High Prevalence of Metabolic Syndrome and Its Related Demographic Factors in North of Iran: Results from the PERSIAN Guilan Cohort Study

Abstract: Introduction. The prevalence of metabolic syndrome has increased in recent decades around the world and is currently reaching epidemic levels as it is a major public health and clinical concern. The aim of this study was to evaluate the prevalence of metabolic syndrome and its related demographic factors in a population-based study. Methods. In this cross-sectional study, the target population consisted of 10520 individuals aged 35–70 years in Phase 1 of the Persian Guilan cohort study (Guilan site/Some’e Sara… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 52 publications
3
16
0
Order By: Relevance
“…The prevalence of general and central obesity in our study was 66.0% and 45.33%, respectively. The prevalence of central obesity in the Persian Guilan cohort study (Guilan site/Some'e Sara) on 10,520 individuals aged 35-70 years was 75.8% [26].…”
Section: Discussionmentioning
confidence: 95%
“…The prevalence of general and central obesity in our study was 66.0% and 45.33%, respectively. The prevalence of central obesity in the Persian Guilan cohort study (Guilan site/Some'e Sara) on 10,520 individuals aged 35-70 years was 75.8% [26].…”
Section: Discussionmentioning
confidence: 95%
“… 41 42 In Iran, multiple studies reported the prevalence of Mets differently; 34.7% by NCEP ATP III and 37.4% by IDF, 43 37% by IDF and 33.8% by NCEP ATP III, 44 42.87% by IDF and 40.68% by NCEP ATP III. 45 According to the Isfahan Healthy Heart Program, the age-adjusted prevalence of Mets was reported to be 23.3% according to the NCEP ATP III definition in urban and rural populations of three cities of Iran. 41 In all definitions, except WHO, the prevalence of Mets was higher in women.…”
Section: Discussionmentioning
confidence: 99%
“…Mets is considered as a frequent disorder in Iranian population as well,40 and people living in urban areas were recognised as more risky ones in comparison with rural residents 41 42. In Iran, multiple studies reported the prevalence of Mets differently; 34.7% by NCEP ATP III and 37.4% by IDF,43 37% by IDF and 33.8% by NCEP ATP III,44 42.87% by IDF and 40.68% by NCEP ATP III 45. According to the Isfahan Healthy Heart Program, the age-adjusted prevalence of Mets was reported to be 23.3% according to the NCEP ATP III definition in urban and rural populations of three cities of Iran 41.…”
Section: Discussionmentioning
confidence: 99%
“…These risk factors include waist circumference; high triglyceride; lower HDL cholesterol; high blood pressure or previously diagnosed hypertension; high fasting plasma glucose (≥100 mg/dl) or previous diagnosis of type 2 diabetes. 2 , 8 According to the National Diabetes Statistics Report, a periodic publication of the Centers for Disease Control and Prevention (CDC) published in 2020, about 34.2 million people of all ages (10.5% of the US population) had diabetes. About 34.1 million adults aged 18 years or older (or 13.0% of all US adults) had diabetes.…”
Section: Introductionmentioning
confidence: 99%